Deja Vu : Aberrations Of Cultural Memory - Krapp, Peter (Book collections on Project MUSE., 2004)
Referring to a past that never was, dejà vu shares a structure not only with fiction, but also with the ever more sophisticated effects of media technology. Tracing the term from the end of the nineteenth century, when it was first popularized in the pages of the Revue philosophique, Peter Krapp examines the genealogy and history of the singular and unrepeatable experience of dejà vu. This provocative book offers a refreshing counterpoint to the cliched celebrations of cultural memory and forces us do a double take on the sanctimonious warnings against forgetting so common in our time. Disturb.